Peran Diaspora Di Masa Pandemi Covid-19 - Lyvie Audrey Ardian (Journal of Citizenship, 2022)
This paper tries to understand the phenomenon of the role of the diaspora in the Covid-19 pandemic. With the current pandemic outbreak, humans are always challenged to carry out various forms of adaptation that allow themselves to remain active and productive from within the home. The term diaspora is often used to denote different phenomena depending on the interests and focus of the study. “Diaspora” are immigrants, namely people who leave their homeland to go to another region or country in search of a better life, rather than in their own region or country. A number of migration and diaspora studies conclude that international migration that occurs in the era of globalization can not only expand the distribution of diaspora, but can also strengthen their existence. Another existence of the diaspora is related to their role in realizing a symbiosis that is beneficial for both the destination country and the country of origin. The Indonesian diaspora has the potential to be empowered for national defense. In this analysis using descriptive qualitative analysis method, using data collection techniques on the study of literature. The diaspora is not only a large global community but an extraordinary movement and idealism. Some parties use the term transnational communities to refer to the experiences of citizens who are doing contemporary migration or who have chosen to move from their country of origin but who still maintain a relationship or relationship with the land where they were born.